Protective properties of stingless bee honey in zebrafish embryo exposed to gamma irradiation - Adenan, Mohd Noor Hidayat (2021)
There are many benefits of ionizing radiation applications particularly in the field of medicine, industry, agriculture and research. As the use increases, the risk of getting health hazards is the major concern if not properly used or contained. Overexposure to ionizing radiation can cause acute health effects or late consequences which is cancer risk. At the cellular level, the radiation will induce DNA damage and after that apoptosis as leading route of cell inactivation. Cells exposed to ionizing radiation can release signals that induce very similar effects in non-targeted neighbouring cells, a phenomenon known as bystander effects. In this study, we have used the zebrafish as the powerful in vivo model organism to evaluate the potential of Kelulut honey (KH) in reducing the harmful effects of gamma irradiation. Several types of honey are well documented to reduce radiation-induced damage in vitro and in vivo. All of the honey were chosen based on antioxidant properties reported in previous studies. None of the studies have discussed on the potential of KH as radioprotectant. Our aim was to investigate the effectiveness of KH in radioprotecting the zebrafish embryo from adverse effects of gamma radiation. Zebrafish embryos were collected according standard guidelines. Briefly, 24 hours post fertilization (hpf) zebrafish embryos were irradiated at the doses of 11 – 20 Gy of gamma ray (caesium-137). The embryos were examined for lethality and abnormalities until 96 hours post-irradiation (120 hours post fertilization). The optimum concentration of KH for zebrafish embryos treatment was obtained through toxicity evaluation. Evaluation of KH for radioprotective properties has been performed by using phenotypic assay and immunohistochemistry analysis involving γH2AX and caspase-3 proteins represented DNA damage and apoptosis. All of the results were were analyzed using two-way ANOVA followed by Tukey post hoc test using GraphPad Prism version 8 and presented as mean ± SEM. Amifostine was used as a positive control for comparison purposes. The dose of KH selected for determination of survival, morphology, DNA damage and apoptosis was 8 mg/mL. KH also was found to be not toxic in the zebrafish embryos depending ii on the concentration used. For lethality evaluation, coagulated zebrafish embryos found at 24 and 48 hours post-irradiation. The highest coagulation were from 19 and 20 Gy of the irradiation and the lowest at 11 Gy. LC50 value of gamma radiation at 120 hpf was 13.68 Gy. Several combinations of abnormality (body curvature, microphthalmia, microcephaly and pericardial oedema) were found in the study. KH treatment was found to increase survival rate up to 20 Gy (p<0.05). It is also found to reduce morphological abnormalities of embryos specifically body curvature incidence. Bystander embryos pre-treated with KH and amifostine were found to reduce lethality and abnormality effect of irradiated-embryo conditioned media (IECM) irradiated. The lethality and abnormality occurrence in the study overall were independent of irradiation doses. Amifostine was identified to reduce DNA damage in the zebrafish embryos at 11 to 20 Gy of gamma irradiation (p<0.05). KH treatment was recorded to be significantly reduced the DNA damage at 14 and 15 Gy of radiation exposure (p<0.05). The DNA damage was only recorded in the bystander zebrafish embryos at 18 and 19 Gy of IECM exposure (p<0.05). Amifostine showed less protective effect to reduce DNA damage at 18 and 19 Gy and KH did not reduce the intensity of γH2AX in the bystander embryos. Similar to DNA damage analysis, amifostine was found to reduce the apoptosis incidence in the zebrafish embryos at 11 to 20 Gy (p<0.05). KH was recorded to reduce the apoptosis at 11, 12, 13 and 15 Gy of the irradiation dose (p<0.05). Caspase-3 intensity was found to be similar at 11 to 18 Gy in all of the bystander embryos which was no apoptosis incidence showed in the analysis. Amifostine was identified to reduce the apoptosis at 20 Gy of IECM exposure and KH was not reduce the apoptosis incidence in the bystander embryos (p<0.05). The collective results suggest that KH exhibited radioprotective properties in zebrafish embryos by reducing the adverse effects of gamma irradiation and can be categorized as the one of potential Type A2 radioprotectant which focused to scavange free radicals by ionizing radiation in the study. Besides, KH can be developed as a future radioprotector.